Nurses’ compliance with the five moments of hand hygiene and healthcare-associated infections - I Gusti Ngurah Aryana; Ni Luh Putu Inca Buntari Agustini; I Ketut Alit Adianta; Putu Noviana Sagitarini; I Gede Putu Darma Suyasa (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Adherence to the five moments of hand hygiene in hospital settings plays a crucial role in preventing healthcare-associated infections (HAIs). Despite the widespread dissemination and acceptance of these guidelines, nurses’ compliance rates remain suboptimal in many healthcare institutions. Numerous factors have been identified as influencing nurses’ adherence to the five moments of hand hygiene. Purpose: To identify factors associated with nurses' compliance with the five moments of hand hygiene in reducing healthcare-associated infections. Method: This study employed a quantitative, non-participatory observational design using a cross-sectional correlational approach. A total of 334 nurses from Prof. Dr. I.G.N.G. Ngoerah General Hospital were recruited as participants. Data were collected through structured questionnaires and analyzed using univariate, bivariate, and multivariate statistical methods. Results: Overall, the compliance rate of nurses with the five moments of hand hygiene was 62.0%. The main factors significantly associated with compliance included the type of treatment room (p = 0.007; AOR = 2.116; 95% CI: 1.225–3.656), belief (p = 0.001; AOR = 16.596; 95% CI: 4.726–58.279), and glove use (p = 0.001; AOR = 5.957; 95% CI: 3.430–10.340). Conclusion: The key determinants affecting compliance with the five moments of hand hygiene include nurses’ beliefs, the use of gloves, and the type of treatment room. Beyond the variables examined in this study, additional predictors such as patient conditions, stress levels, workload, and socio-cultural influences may also contribute to variations in nurses’ adherence to the five moments of hand hygiene.